The Influence of School Committees and Operational Assistance for Educational Units on School’s Quality - Santi, Mega; Harapan, Edi; Pahlawan, Pahlawan (Journal of Social Work and Science Education, 2024)
This study aims to determine whether school committees and educational unit operational assistance influence school quality. This research was carried out at SD Negeri Muara Kuang District, Ogan Ilir Regency. This type of research is quantitative, while the partial correlation method is used. The validity test uses construct validity while the reliability test uses Cronbach’s Alpha. The analysis prerequisite test used the normality test, homogeneity test, linearity test, and multicollinearity test and the data are analyzed using sample regression and multiple regression techniques. The sample in this research is the school committee, principal, and teachers in Negen Elementry School, Muara Kuang District, numbering 61 people. Data collection techniques in this research used questionnaires and documentation. The results of the research conclude that (1) There is an influence of school committees on school quality with a correlation value of 0,109 with a correlation percentage of 1,2% while 98,8% is determined by other factors not mentioned in this research, (2) There is an influence of assistance educational unit operations on school quality with a correlation value of 0,937 with a correlation percentage of 87,8% while 12,2% is determined by other factors not mentioned in this research, (3) There is an influence of the school committees and educational unit operational assistance together on school quality with a correlation value of 0,937 with a relationship percentage of 87,8% while 12,2% is determined by other factors not mentioned in this research.